Calamity Kate - Visaggio, Magdalene; Visaggio, Magdalene (Dark Horse Books, 2019)
Kate Strand reboots her destructive life and moves to LA to be the superhero she always wanted to be--Calamity Kate: gun-toting monster killer. With her latest career change, she faces new challenges, relationships, and competition; desperate to show she's worth a damn in a world overrun by zombies, vampires, demons, goblins, and the ultimate monster bounty: The Seven Fabled Beasts of Yore.